Unexpected synthesis of 3-imino-2-(pyrrol-2-yl) isatogen derivatives affords facile access to a 2-pyrrolyl isatogen. Issue 1 (2nd January 2017) - Kirk, Nicholas S.; Sansom, Geraud N.; Sudta, Pichit; Suksamrarn, Sunit; Willis, Anthony C.; Bremner, John B.; Kelso, Michael J.
ABSTRACT: 2-Aryl isatogens and their 3-imino derivatives have been extensively studied but to date there have been no reported variants carrying pyrrolyl substituents at the 2-position. This study describes the unexpected synthesis of two novel 3-imino-2-(pyrrol-2-yl) isatogen derivatives upon attempted amide couplings with ( E )- or ( Z )-3-(3, 5-dimethyl-1 H -pyrrol-2-yl)-2-(2-nitrophenyl)acrylic acids and p -phenylenediamines in the presence of uronium-based coupling reagents. Imine hydrolysis of one derivative under mild acid conditions afforded a 2-pyrrolyl isatogen in high yield. The compound showed potent in vitro antiplasmodial activity against Plasmodium falciparum. GRAPHICAL ABSTRACT: